A study of the diffusion dynamics and concentration distribution of gold nanospheres (GNSs) without fluorescent labeling inside live cells using fluorescence single particle spectroscopy. Issue 11 (5th March 2018) - Liu, Fangchao; Dong, Chaoqing; Ren, Jicun
Abstract : A single particle fluorescence correlation spectroscopy method to study the concentration distribution of folic acid-modified GNSs (FA-GNSs) internalized via folate receptors and investigate their diffusion dynamics within live cells. Abstract : Colloidal gold nanospheres (GNSs) have become important nanomaterials in biomedical applications due to their special optical properties, good chemical stability, and biocompatibility. However, measuring the diffusion coefficients or concentration distribution of GNSs within live cells accurately without any extra fluorescent labeling in situ has still not been resolved. In this work, a single particle method is developed to study the concentration distribution of folic acid-modified GNSs (FA-GNSs) internalized via folate receptors, and investigates their diffusion dynamics within live cells using single particle fluorescence correlation spectroscopy (FCS). We optimized the experimental conditions and verified the feasibility of 30 nm GNSs without extra fluorescence labeling being used for single particle detection inside live cells. Then, the FCS characterization strategy was used to measure the concentration and diffusion coefficient distributions of GNSs inside live cells and the obtained results were basically in agreement with those obtained by TEM. The results demonstrate that our strategy is characterized as an in situ, nondestructive, rapid and dynamic method for the assay of live cells, and it may be widely used in the further design of GNP-based drug delivery and therapeutics.